The structural logical scheme of development hydrocarbons’ trouble emissions and main demands to sorbents which are used for their liquidation on the railway transport - Soroka, M. L.; Yaryishkina, L. A. (Science and Transport Progress, 2011)
The processes and factors associated with the development of emergency emissions of hydrocarbons during their transportation by rail are considered in the article. Basic requirements to sorbents used to eliminate emergency emissions of hydrocarbons on railway transport are offered.